2011
DOI: 10.1007/s11431-011-4339-7
|View full text |Cite
|
Sign up to set email alerts
|

Singular value diagnosis in dam safety monitoring effect values

Abstract: Based on the principal component analysis, principal components that have major influence on data variance are determined by the energy percentage method according to the correlation between monitoring effects. Then principal components are extracted through reconstructing multi effects. Moreover, combining with the optimal estimation theory, the method of singular value diagnosis in dam safety monitoring effect values is proposed. After dam monitoring information matrix is obtained, single effect state estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Dam displacement is taken as an example. For the dam displacement caused by the action of water load, temperature load, and other loads, it can be divided into water level component δ H , temperature component δ T and aging component δ θ , namely δ=δH+δT+δθ. …”
Section: Svm‐based Static Model Monitoring Dam Safetymentioning
confidence: 99%
“…Dam displacement is taken as an example. For the dam displacement caused by the action of water load, temperature load, and other loads, it can be divided into water level component δ H , temperature component δ T and aging component δ θ , namely δ=δH+δT+δθ. …”
Section: Svm‐based Static Model Monitoring Dam Safetymentioning
confidence: 99%
“…Principal component analysis has been applied in multivariate analysis, structural health analysis, modal analysis, parameter identification, and structural damage detection . In this work, it will be shown that this technique can be very useful in the selection of the thermometers that best represent the thermal effect in the statistical model for prediction of horizontal displacements in concrete dams.…”
Section: Principal Component Analysis: An Overviewmentioning
confidence: 99%
“…Some research work has demonstrated that the prototype monitoring data series on dam behavior has chaotic characteristics. 9,10 The unordered chaotic time series presents a certain regularity, which is sensitive to initial value. It is difficult to forecast the long-term behavior according to chaotic time series.…”
Section: Introductionmentioning
confidence: 99%